Performance Communications Medical Services and Non- Medical In-Process Medical Treatment Islamic Hospital Sultan Agung Semarang - Putri Tristanti, Juita; Naryoso, S.Sos, M.Si, Agus (Interaksi Online, 2016)
Failure to communicate is one of the root causes of the most common causes of patient safety incidents. Communication determining success in helping to resolve the patient's health problems. Performance communication services medical or nonmedical personnel in the process of medical treatment is part of a health communication. Health communication is a communication process that involves health messages, elements or participant communication. Semarang Sultan Agung Islamic Hospital is a private hospital grade B. The hospital is able to provide services of medical specialists and subspecialists limited. The purpose of this study was to determine the communication performance of medical and non medical services in the process of medical treatment RSI Sultan Agung Semarang. The theory of reputation used to determine how performance should be owned by a health-care facility, which especially its RSI Sultan Agung Semarang as research objects. The population used is the patient who is in Islam Sultan Agung Hospital Semarang with criteria outpatients from a specialist, and already control at least 3 times, which in total amounted to 97 people. Research shows the majority of respondents expressed satisfaction with the communication performance of medical and non medical services RSI Sultan Agung. However, there are also consumers RSI Sultan Agung Semarang who felt unserved optimal communication of medical or non-medical RSI Sultan Agung Semarang. The study then provides suggestions for RSI Sultan Agung Semarang can further improve the performance of the communication performance of medical and non medical personnel to give more comfort to patients and consumers as a whole.